Effect of HUK on the outcome of ruptured intracranial aneurysm. Issue 10 (29th August 2018) - Chen, Luyue; Lyu, Yi; Lin, Xiaoning; Sun, Minghui; Feng, Wei; Tian, Xinhua
Abstract: Objective: To evaluate the clinical efficacy of Human Urinary Kallidinogenase (HUK) on the outcome of patients with ruptured intracranial aneurysm. Methods: This was a prospective, open‐label study. At the Department of Neurosurgery in our hospital, 127 patients were treated and operated due to ruptured intracranial aneurysm in the period 2015–2016. After surgery, all the patients received basic treatment and 70 patients received additional HUK treatment (HUK group) according to their willing. In detail, 0.15 PNA unit of HUK injection plus 100 ml saline in intravenous infusion was performed, with once a day for 14 consecutive days. The modified Rankin Scale (mRS) scores and favorable mRS rates (mRS 0–1) were analyzed 3‐month after the treatment. Results: No difference was shown in the basic characteristics between the two groups ( p > 0.05). Favorable mRS rate in the HUK group (71.43%) was significantly higher than that in control group (50.88%, p < 0.05). In addition, 3‐month death rate was significantly lower in the HUK group. Delayed ischemic stroke rate was similar between the two groups. Conclusion: HUK can reduce morbidity and mortality of patients with ruptured intracranial aneurysm after surgery. Abstract : Favorable mRS rate in the HUK group (71.43%) was significantly higher than that in control group (50.88%, p < 0.05). 3‐month death rate was significantly lower in the HUK group. HUK can reduce morbidity and mortality of patients with ruptured intracranial aneurysm.